2021
DOI: 10.3389/fonc.2021.777356
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanocrystal Injection of Insoluble Drug Anlotinib and Its Antitumor Effects on Hepatocellular Carcinoma

Abstract: The molecularly targeted agent anlotinib offers a novel therapeutic strategy against advanced hepatocellular carcinoma (HCC). With this study, we aimed to solve the technical problem of anlotinib being insoluble in injectable solutions; we also aimed to assess the antitumor activity of anlotinib on hepatocellular carcinoma cells. We prepared an anlotinib nanocrystal injection by wet grinding, and we optimized the prescription process using a transmission electron microscope (TEM) and a laser particle size anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Intravenous injection can be applied to overcome the problems from oral administration and thus obtain satisfactory therapeutic efficacy with a lower dose. A representative study on the intravenous injection of the anti-HCC agent anlotinib was performed by Luo et al [ 58 ], which showed that a greatly reduced dose (1/10 of the oral dose) produced a significantly improved anti-HCC effect.…”
Section: Icaritin-based Nanomedicines For Improved Immunotherapy Of A...mentioning
confidence: 99%
“…Intravenous injection can be applied to overcome the problems from oral administration and thus obtain satisfactory therapeutic efficacy with a lower dose. A representative study on the intravenous injection of the anti-HCC agent anlotinib was performed by Luo et al [ 58 ], which showed that a greatly reduced dose (1/10 of the oral dose) produced a significantly improved anti-HCC effect.…”
Section: Icaritin-based Nanomedicines For Improved Immunotherapy Of A...mentioning
confidence: 99%
“…On this basis, the four selected cytotoxic chemotherapy drugs, gemcitabine, paclitaxel, etoposide or doxorubicin, all act on biological macromolecules such as DNA and microtubules, and kill malignant tumor cells by causing macromolecular damage [59][60][61][62]. Among the selected four molecularly-targeted drugs, gefitinib, erlotinib and osimertinib, all mainly act on the EGFR, while anlotinib is a multi-target protein kinase inhibitor that targets the VEGFR [63,64]. Gefitinib is considered the first-generation of small molecule protein kinase inhibitors acting on EGFR, while erlotinib and osimertinib are the second-and third-generation agents acting on small molecule protein kinase inhibitors [63,64]; all these drugs were used in this study and killed A549 cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Among the selected four molecularly-targeted drugs, gefitinib, erlotinib and osimertinib, all mainly act on the EGFR, while anlotinib is a multi-target protein kinase inhibitor that targets the VEGFR 63 , 64 . Gefitinib is considered the first-generation of small molecule protein kinase inhibitors acting on EGFR, while erlotinib and osimertinib are the second- and third-generation agents acting on small molecule protein kinase inhibitors 63 , 64 ; all these drugs were used in this study and killed A549 cells in a dose-dependent manner. These drugs mainly act on the EGFR and the difference in their activity is mainly determined by the higher mutational status of the EGFR 64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prolonged oral administration of this drug not only results in a low bioavailability but also induces multi‐drug resistance (MDR) in cancer cells. Therefore, Luo et al employed poloxamer 188 and egg yolk lecithin as the charge stabilizer and space stabilizer, respectively, to fabricate anlotinib nanocrystals through a ball milling method (Luo et al, 2021). The optimal nanocrystals, characterized with a uniform average particle size of 200 nm and a zeta potential of −30 mV, were obtained through continuous grinding using a high shear emulsifying homogenizer for a duration of 90–120 min.…”
Section: Recent Development Of Nanocrystals With Different Administra...mentioning
confidence: 99%